Use of novel oral anticoagulants for the treatment of venous thromboembolism and its considerations in Asian patients - Lee, Yun-Jeong (Dove Medical Press, 2014)
Parenteral anticoagulation followed by warfarin has been conventionally used for the treatment of venous thromboembolism (VTE). However, there are numerous troublesome characteristics of warfarin that prompted the development of novel oral anticoagulants (NOACs) for the treatment of VTE. Asians are reported to be at an increased risk of bleeding with warfarin, and while the reported incidence of VTE in Asians is lower than in Caucasians, the annual rate of VTE in Asia is rising along with the need for better oral anticoagulant options. Recently, several Phase III clinical trials with NOACs for the treatment and prevention of VTE recurrence have been published. For the treatment of VTE, the four NOACs – dabigatran, rivaroxaban, apixaban, and edoxaban – each showed comparable efficacy outcomes while resulting in better safety outcomes when compared with conventional treatment. In these trials, Asian patients had comparable efficacy and safety outcomes as other races, except in the edoxaban trial, in which the Asian subgroup had better safety profiles than other races, although further confirmation is necessary. For secondary prevention, dabigatran was compared with conventional treatment and showed similar efficacy and safety outcomes. When NOACs were compared with placebo for secondary prevention of VTE, they showed superior efficacy and increased bleeding except for apixaban, which showed comparable major bleeding and composite of major and clinically relevant nonmajor bleeding rates as placebo. No significant differences in the outcomes based on race were observed in the Asian subgroups for secondary prevention. Therefore, NOACs can be used with similar efficacy and at least similar or superior safety compared with conventional treatment in the treatment of VTE, and at no increased risk in Asian patients.